Functional feeding habits of Chironomidae larvae (Insecta, Diptera) in a lotic system from Midwestern region of São Paulo State, Brazil - Silva, Fabio L.; Ruiz, Sonia S.; Bochini, Gabriel L. [UNESP]; Moreira, Diana C. [UNESP] (My University, 2008)
Functional feeding habits of Chironomidae larvae (Insecta, Diptera) in a lotic system from Mid-western region of São Paulo State, Brazil were analyzed. Collectors were the dominant organisms, repre-sented by genera Chironomus, Fissimentum and Cryptochironomus, following by shredders and predators.
Keywords: Diet; Food habits; Functional feeding groups; Gut contents; Chironomidae; Cryptochironomus; Diptera; Insecta